2015
DOI: 10.1007/s12022-015-9388-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of TSHR and TP53 Genes in an Aggressive Clear Cell Follicular Carcinoma of the Thyroid

Abstract: Clear cell follicular carcinoma is a rare type of thyroid cancer and some with aggressive biological behavior. The cytoplasmic clearing of the neoplastic cells has been attributed to the accumulation of various substances, such as glycogen, lipid, mucin, and thyroglobulin, or distension of mitochondria or endoplasmic reticulum. However, the molecular mechanisms responsible for the characteristic appearance of the cell cytoplasm and the biological behavior remain unknown. We report here a case of aggressive cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Subsequently, we tried to select genes that were differentially expressed between PTCs in cluster 1 and BRAF wild PTCs in cluster 2 (see Figure ). Unfortunately, we did not observe high expression of well‐known genes, such as BRAF , TERT , RAS , RET , TP53 , NTRK1 , or NTRK3 . We selected 100 differentially expressed genes by statistical analysis using paired the t test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we tried to select genes that were differentially expressed between PTCs in cluster 1 and BRAF wild PTCs in cluster 2 (see Figure ). Unfortunately, we did not observe high expression of well‐known genes, such as BRAF , TERT , RAS , RET , TP53 , NTRK1 , or NTRK3 . We selected 100 differentially expressed genes by statistical analysis using paired the t test.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not observe high expression of well-known genes, such as BRAF, TERT, RAS, RET, TP53, NTRK1, or NTRK3. [32][33][34][35][36][37] We selected 100 differentially expressed genes by statistical analysis using paired the t test. Although certain genes might not have significant functional roles, if the functional location of that gene is just upstream or just downstream of functionally important genes, such functionally insignificant genes can be selected as prediction markers.…”
Section: Discussionmentioning
confidence: 99%
“…Gain-of-function mutation of TSHR might also contribute to the development of clear cell appearance in thyroid tumors [42]. Clear cell variants of follicular adenoma/carcinoma, oncocytic cell tumors, and papillary and medullary thyroid carcinoma have been recognized in the 2017 World Health Organization classification [2].…”
Section: Follicular Neoplasms With Clear Cell Changementioning
confidence: 99%
“…Traditionally, clear cell variants of thyroid carcinomas have not been linked to any biological aggressiveness. However, an aggressive clear cell variant of follicular thyroid carcinoma combining a putative gain of function of TSHR and a loss-of-function TP53 has also been reported [ 42 ].…”
Section: Tumors With Predominant Follicular Growth Patternmentioning
confidence: 99%
“…TERT promoter mutations have been observed in 5% to 25% of DTC, and it’s been reported that TERT promoter mutations contribute to aggressive behavior in DTC ( 20 , 21 , 22 ). These mutations have a significantly higher prevalence in aggressive thyroid tumor types such as widely invasive oncocytic carcinomas, poorly differentiated carcinomas, and anaplastic thyroid carcinomas (ATC) ( 23 ). Similarly, TP53 mutations are prevalent in advanced tumors with a higher recurrence ( 24 ).…”
Section: The Age Of Genomicsmentioning
confidence: 99%